Gaya Mengajar Guru PNS dan Honorer di Sekolah Dasar Negeri 55/I Sridadi, Jambi - Faizal Chan; Agung Rimba Kurniawan; Sutria Ningsih; Khairul Amri; Ari Surya Febriana; Novita Wisudawati; Vina Sandra Irani (Universitas Negeri Padang, 2019)
The aim of this research is to describe the teaching style of the servant and honorarium teacher in elementary school number 55/I Sridadi on years 2019/2020. This research use qualitative descriptive. The collecting of the data were use observation and interview. Interview were do with servant, honorarium and head master in elementary school number 55/I Sridadi, Analysis data was use interactive model (Miles and Huberman) and to test the validity data use triangulation data. The result from this research got there is differentiate among servant and honorarium teacher in teaching style in elementary school number 55/I Sridadi on years 2019/2020.